Um estudo sobre os diferenciais de remuneração entre os professores das redes pública e privada de ensino - Barbosa Filho, Fernando de Holanda; Pessôa, Samuel de Abreu; Afonso, Luís Eduardo (Estudos Econômicos (São Paulo), 2009)
This paper studies the earnings differentials between public and private professors in the different levels of education. In most of the cases, there is a positive differential in favor of the private sector. This conclusion changes when we compute the Present Value of the Work Contract (PVWC). The PVWC considers all the income received during the workers life span. Here, we compute the present value of the wages received in the working life with the retirement benefits. The results show that the PVCW is higher in the public sector than in the private sector. We compute the internal rate of return (IRR) of the retirement system. We conclude that different retirement rules between the two sectors have a huge impact in the professors´ life earnings with a public IRR higher than the private one. We also conclude that public teachers do not receive lower earnings than their private counterparts.